2014
DOI: 10.1016/j.stem.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the In Vivo Origin of Metanephric Nephron Progenitors Enables Generation of Complex Kidney Structures from Pluripotent Stem Cells

Abstract: Recapitulating three-dimensional (3D) structures of complex organs, such as the kidney, from pluripotent stem cells (PSCs) is a major challenge. Here, we define the developmental origins of the metanephric mesenchyme (MM), which generates most kidney components. Unexpectedly, we find that posteriorly located T(+) MM precursors are developmentally distinct from Osr1(+) ureteric bud progenitors during the postgastrulation stage, and we identify phasic Wnt stimulation and stage-specific growth factor addition as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

34
803
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 736 publications
(874 citation statements)
references
References 51 publications
34
803
3
1
Order By: Relevance
“…2 It took some time for this uncontrolled in vivo potential to be translated into highly directed and controlled in vitro differentiation of pluripotent stem cells toward renal lineages. 3,4 The understanding of how the mammalian kidney develops in vivo laid the foundation for deciphering the inductive signals required for the in vitro directed renal differentiation protocols from pluripotent stem cells. For instance, Six21Cited11 nephron progenitors residing in the nephrogenic cortex were shown to give rise to all types of nephron epithelia.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…2 It took some time for this uncontrolled in vivo potential to be translated into highly directed and controlled in vitro differentiation of pluripotent stem cells toward renal lineages. 3,4 The understanding of how the mammalian kidney develops in vivo laid the foundation for deciphering the inductive signals required for the in vitro directed renal differentiation protocols from pluripotent stem cells. For instance, Six21Cited11 nephron progenitors residing in the nephrogenic cortex were shown to give rise to all types of nephron epithelia.…”
mentioning
confidence: 99%
“…Nishinakamura and colleagues 3 further translated knowledge of early kidney development into an efficient differentiation protocol; they were able to separate anterior from posterior intermediate mesoderm in the early stages of renal differentiation. 3 Although a transcription factor T (also known as Brachyury) is mainly expressed in the immature mesoderm of the primitive streak at E7.5, Nishinakamura and colleagues 3 found that the precursors of nephron progenitors remained as T1 immature cells at the posterior end of E8.5 embryos. These cells convert to Osr11 posterior intermediate mesoderm at E9.5, whereas the ureteric bud precursors convert from T1 to Osr11 anterior intermediate mesoderm 1 day earlier (E8.5).…”
mentioning
confidence: 99%
See 3 more Smart Citations